Atividade docente : implicações ético-formativas - Silva, Fabio Hebert da (2011)
This thesis examines the relationship between teaching activities, formation and ethics in the context of some research experience in education, from the dialogue with literature, philosophy, stories of teachers, field diaries and research reports. The themes relate in the text to write some guidelines for an evaluation of methods of intervention in the processes of work in schools and research experience, considering the production of spaces for analysis of work processes. The theme of the formation examines the relationship between ongoing processes and procedures that point to the prospect of collective analysis of work processes. The ethical perspective is brought as the evaluation of the effects that certain sets of practices have produced, both in relation to the teacher and researcher. The research experience through the relationship between teaching activities, formation and ethics. The methodological issue gains importance in this sense in trying to turning in work processes and formation. We note as well, the nature of codependent relationship between the researcher and the teacher's activity, the formation of a researcher and teacher in what (and what) they do. And inspired by Bergson, we call intuition as a method of preparing and modulation of a science of real and alive, precisely because of his procedural dimension - manufacturing and invention.